Інтелектуальна система для аналізу та підбору комп'ютерних компонентів - Харченко, В. В. (ХНУРЕ, 2024)
The application revolves around simplifying the process of selecting computer components and ensuring their compatibility. Starting with the Component Compatibility Checker, users input their desired components, and the system verifies their compatibility. For further assistance, the Compatibility Advisor provides insights into why certain components may not align and offers solutions Besides of algorithm of analyzing compatibility The integrated artificial intelligence analyzes user configurations and proposes suitable substitutions if it detects potential conflicts or bottlenecks. This allows picking an optimal set of components, avoiding performance issues, and saving time finding the most efficient configuration. During the selection process, the Real-time Compatibility Scanner provides instant feedback on component compatibility.
Keywords: комп'ютерні компоненти; система підбору